1288. US Healthcare Provider Perspectives on the initiation of cabotegravir and rilpivirine long-acting (CAB+RPV LA) in an observational real-world study (BEYOND). (15th December 2022) - Hsu, Ricky K; Phoenix, John; Sinclair, Gary I; Gupta, Samir K; Puga, Ana; Nguyen, Kaitlin; Schubert, Catherine K; Merrill, Deanna; Richardson, David; Nelson, Kate; Reynolds, Maria; Zografos, Laurie; et al.
Abstract: Background: CAB+RPV LA is a complete regimen for treatment of virologically suppressed people with HIV (PWH). As an injectable therapeutic administered by a healthcare provider (HCP), CAB+RPV LA may alleviate challenges with adherence to daily oral therapy and reduce fear of HIV status disclosure with oral treatment. Real world perspectives from HCPs and PWH are needed to enable successful delivery of this treatment in US healthcare settings. Methods: BEYOND is a 2 year prospective, observational, real-world study of utilization, outcomes, and experience of PWH initiating CAB+RPV LA across 30 US sites. HCPs at participating sites (treaters, injectors, drug acquisition/reimbursement staff) completed surveys at site activation (Sep 2021-Feb 2022; with follow-up surveys planned at 6, 12, 24 months) evaluating experiences to date with implementation of CAB+RPV LA at their sites. Results: HCPs from 24 sites responded to the initial survey (Table 1). 75% of HCPs estimated that ≥25% of their PWH are eligible for CAB+RPV LA, and 71% of sites are proactively discussing the regimen with ≥25% of PWH. The majority (79%) of treaters reported they were extremely/very positive about administering CAB+RPV LA. Over 90% of injectors reported a positive overall opinion about administering CAB+RPV LA, and 86% reported the injections were easy to administer. Most (87%) HCPs reported injection visits taking ≤45 minutes, including waiting time. Over 95% of sites have patient reminder systems; 86% will manually identify missed injections and all reported manual follow up by site staff. All sites utilizing the injection education video on the external HCP website (n=15/15) found it helpful and 94% (n=16/17) utilizing reimbursement specialists found them to be helpful. In their experience to date, most clinics reported only needing to increase coordination with the pharmacy team and add injection training to implement CAB+RPV LA. The most frequently reported benefits of implementing CAB+RPV LA by HCPs included assurance of patient adherence and patient engagement in their HIV treatment (Table 2). Conclusion: Early real-world data from US HCPs in this study indicates interest in and anticipated uptake of CAB+RPV LA at their sites, positive overall opinion, and multiple benefits of administering the CAB+RPV LA regimen to PWH. Disclosures: Ricky K. Hsu, MD, Gilead: Honoraria|Merck: Honoraria|ViiV: Advisor/Consultant|ViiV: Grant/Research Support|ViiV: Honoraria John Phoenix, MSN, APRN, FNP-C, Gilead Sciences: Advisor/Consultant|Gilead Sciences: Honoraria|Gilead Sciences: speaker bureau, research funding|Janssen Pharmaceutical: Advisor/Consultant|Janssen Pharmaceutical: Honoraria|Lupin Pharmaceuticals: Advisor/Consultant|Lupin Pharmaceuticals: Honoraria|Napo pharmaceutical: Honoraria|Napo pharmaceutical: speaker bureau|Scinexis: Advisor/Consultant|Scinexis: Honoraria|ViiV Healthcare: Advisor/Consultant|ViiV Healthcare: Honoraria|ViiV Healthcare: speaker bureau, clinical research funding Gary I. Sinclair, MD, ABBVIE: Grant/Research Support|Gilead: Grant/Research Support|Janssen: Advisor/Consultant|Janssen: Grant/Research Support|Janssen: Honoraria|Merck: Grant/Research Support|Thera: Grant/Research Support|Thera: Honoraria|ViiV/GSK: Advisor/Consultant|ViiV/GSK: Grant/Research Support|ViiV/GSK: Honoraria Samir K. Gupta, MD, Gilead Sciences: Advisor/Consultant|GSK/ViiV: Advisor/Consultant|GSK/ViiV: Grant/Research Support Ana Puga, MD, FAAP, AAHIVS, Care Resource: Healthcare provider (HCP)|ViiV Healthcare: Stocks/Bonds Kaitlin Nguyen, PharmD, AAHIVE, ViiV Healthcare: Stocks/Bonds Catherine K. Schubert, PharmD, ViiV Healthcare: Stocks/Bonds Deanna Merrill, PharmD, MBA, AAHIVP, ViiV Healthcare: Salaried employee|ViiV Healthcare: Stocks/Bonds David Richardson, BA, ViiV Healthcare: ViiV provided funding to RTI for the development of the study materials, the conduct of the study, and analysis & interpretation of study results. Kate Nelson, M.Ed, ViIV: ViiV provided funding to RTI for the development of the study materials, the conduct of the study, and analysis & interpretation of study results. Maria Reynolds, MStat, ViiV Healthcare: Viiv provided funding to RTI for the development of the study materials, the conduct of the study, and analysis & interpretation of study results. Laurie Zografos, BS, Viiv: ViiV provided funding to RTI for the development of the study materials, the conduct of the study, and analysis & interpretation of study results. Ashley Jean-Louis, MPH, ViiV Healthcare: (ViiV provided funding to RTI for the development of the study materials, the conduct of the study, and analysis & interpretation of study results.) Cindy Garris, MS, ViiV Healthcare: Employee|ViiV Healthcare: Stocks/Bonds.